Coil Combination Using OpTIMUS Results in Improved Signal‐to‐Noise Ratios of In Vivo MR Spectra Acquired at 7 T - Martinez Luque, Eva; Sung, Dongsuk; Risk, Benjamin B.; Goldberg, Rachel M.; Fleischer, Candace C. (NMR in biomedicine, 2025)
ABSTRACT Magnetic resonance spectroscopy (MRS) enables noninvasive quantification of metabolites, but its utility in vivo can be limited by low signal‐to‐noise ratios (SNRs) and long acquisition times. The use of ultrahigh‐field (UHF) strengths (> 3 T) combined with multichannel phased receive arrays can improve spectral SNR. A crucial step in the use of multichannel arrays is the combination of spectra acquired from individual coil channels. We previously developed a coil combination method at 3 T, optimized truncation to integrate multichannel MRS data using rank‐R singular value decomposition (OpTIMUS), which uses noise‐whitened windowed spectra and iterative rank‐R singular value decomposition (SVD) to combine multichannel MRS data. Here, we evaluated OpTIMUS for combination of MR spectra acquired using a multichannel phased array at 7 T and compared spectral SNR and metabolite quantification with spectra combined using whitened SVD (WSVD), signal/noise squared (S/N2), and the Brown method. Data were acquired from 14 healthy volunteers, including five with data acquired at both 3 and 7 T, and from nine people living with HIV. Spectra combined using OpTIMUS resulted in a higher SNR compared to the three other methods, consistent with our prior results at 3 T. With half the number of averages (N = 32), spectra combined with OpTIMUS had higher SNR compared to spectra using the Brown method with 64 averages. Additionally, spectra combined using OpTIMUS at 7 T were compared to spectra acquired at 3 T with the same number of averages (N = 64) or matched acquisition times (N = 110 averages), and spectral fitting was consistently improved at 7 T even when comparable SNR was obtained at 3 T. The ability to increase SNR and maintain spectral quality by optimizing spectral coil combination has the potential to reduce scan time, a key challenge for routine clinical use of MRS. Coil combination with OpTIMUS increases SNR of MR spectra at 7 T compared to well‐established coil combination algorithms without compromising spectral quantification. By reducing spectral noise and incorporating the metabolic signal from higher order singular vectors, OpTIMUS has the potential to enable shorter acquisition times compared to the default combination provided by the vendor. OpTIMUS implementation for MR spectra acquired from both healthy volunteers and patients supports practical utility across multiple brain regions.